APPEAL OF CITIZENS AS A MEANS OF PROVIDING LEGALITY OF PUBLIC ADMINISTRATION ACTIVITIES - Starodubtsev, A. A. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
the article discusses the major appeals of citizens and regulating legal relations in this field; the level of practical realization of the citizens of Ukraine allocated to them by law the right to make a proposal public authorities; describes the concept of «citizens» appeals, their common features and specific features; certain rights to appeal.